PENGARUH ROA, TATO, DER, EPS DAN CR TERHADAP RETURN SAHAM PERUSAHAAN FARMASI PERIODE 2018-2021 - Ling Ling Ferdian Imara Ferdian; Rendra Erdkhadifa Erdkhadifa (Jurnal Riset Akuntansi, 2023)
Medicines and medical devices are one of the important needs during the Covid-19 pandemic. This has triggered pharmaceutical companies to become one of the investment targets for investors. However, it turns out that pharmaceutical companies have not been able to provide the expected stock returns. This study aims to determine the effect of return on assets, total asset turnover, debt to equity ratio, earnings per share and current ratio on stock returns of pharmaceutical companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The research method used is associative quantitative. This study uses panel data regression analysis. The sampling technique was purposive sampling, so that 7 pharmaceutical companies were obtained as research samples. The results of this study indicate that simultaneously return on assets, total asset turnover, debt to equity ratio, earnings per share and current ratio have a significant effect on stock returns. Furthermore, partially only earning per share has a significant effect on stock returns. Meanwhile, return on assets, total asset turnover, debt to equity ratio and current ratio have no significant effect on stock returns.